Optimizing MSME sustainability through digital marketing, innovation, and financial literacy with financial technology support - Rahmani, Shinta; Abdillah, Fatimah; Ristanti, Vivi (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to analyze the influence of digital marketing, business innovation, and financial literacy on the sustainability of MSMEs in Malang City, with financial technology (fintech) adoption as a mediating variable. Method – This study is a quantitative research with primary data in the form of a questionnaire. Using a purposive sampling technique, data were collected from 120 MSME actors in the culinary, fashion, crafts, and creative services sectors. Analysis was conducted using structural equation modeling–partial least squares (SEM-PLS) via SmartPLS 4.0. Findings – The results show that digital marketing, business innovation, and financial literacy positively and significantly affect MSME sustainability. Financial technology adoption also directly influences sustainability and significantly mediates the relationship between digital marketing and sustainability. However, it does not significantly mediate the relationship between business innovation or financial literacy and sustainability, indicating the need for better alignment between innovation and financial knowledge with financial technology usage. Implications – Theoretically, this study enriches the literature by integrating organizational innovation theory and the technology acceptance model (TAM), offering a comprehensive model of MSME sustainability. Practically, the findings guide MSME actors in strengthening digital marketing strategies and adopting financial technology-based financial management. Local governments are encouraged to implement integrated digital and financial literacy programs, while financial technology providers are advised to improve user education and experience for MSMEs, especially those less familiar with technology. These findings provide actionable insights for building inclusive, tech-savvy, and sustainable MSMEs in the digital economy.